Isolation and Molecular Detection of Salmonella Infantis from Milk and Children with Gastroenteritis in Babylon Province, Iraq - Niran Kadhim F. Al-Rubaey1 , Alyaa Mohammed H. Al-Tabtabai2 , Khaleid Yassen Al-Zamily3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Two hundred and ten samples were included in this study. The samples encompassing of 90 cattle milksamples obtained from local markets, and 120 stool samples obtained from children with gastroenteritisof age less than 12 years from both genders who were attending to the Babylon maternity and children’shospital. The samples were collected during the interval from February to August 2018 in Babylon province.All these 210 samples were subjected to many tests for isolation and identification of Salmonella species byusing bacterial culturing, biochemical tests, and API20E test system. The results showed that the prevalenceof identifying Salmonella isolates were 69 (32.9%) out of 210 samples, distributed as (25/90) (27.8%) marketmilk and (44/120) (36.7%) stool samples. The identified Salmonella isolates were subjected to serotyping bymonovalent antisera. It was found that 4 out of 25 isolates (16%) in market milk samples and 16 out of 44isolates (36.4%) in stool samples that belong to Salmonella infantis. PCR technique was achieved to identifyinvA and invF virulence genes in Salmonella infantis strains. All 20 isolates of Salmonella infantis in marketmilk and stool samples were examined. The results revealed that, invA gene was detected in all strains ofSalmonella infantis isolated from the market milk and stool samples, while the invF gene was present in2 strains of the market milk Salmonella infantis, but existing in all strains of the stool Salmonella infantis.